Measuring Experience With End-of-Life Care: A Systematic Literature Review - Lendon, Jessica Penn; Ahluwalia, Sangeeta C.; Walling, Anne M.; Lorenz, Karl A.; Oluwatola, Oluwatobi A.; Anhang Price, Rebecca; Quigley, Denise; Teno, Joan M. (Journal of pain and symptom management, 2015)
Increasing interest in end-of-life care has resulted in many tools to measure the quality of care. An important outcome measure of end-of-life care is the family members' or caregivers' experiences of care. To evaluate the instruments currently in use to inform next steps for research and policy in this area. We conducted a systematic review of PubMed, PsycINFO, and PsycTESTS® for all English-language articles published after 1990 using instruments to measure adult patient, family, or informal caregiver experiences with end-of-life care. Survey items were abstracted and categorized into content areas identified through an iterative method using three independent reviewers. We also abstracted information from the most frequently used surveys about the identification of proxy respondents for after-death surveys, the timing and method of survey administration, and the health care setting being assessed. We identified 88 articles containing 51 unique surveys with available content. We characterized 14 content areas variably present across the 51 surveys. Information and care planning, provider care, symptom management, and overall experience were the most frequent areas addressed. There was also considerable variation across the surveys in the identification of proxy respondents, the timing of survey administration, and in the health care settings and services being evaluated. This review identified several comprehensive surveys aimed at measuring the experiences of end-of-life care, covering a variety of content areas and practical issues for survey administration. Future work should focus on standardizing surveys and administration methods so that experiences of care can be reliably measured and compared across care settings.